Exploring Global Patterns and Research Frontiers of STEM in Early Childhood: A Bibliometric Analysis - Idhayani, Nurul; Sulfasyah, Sulfasyah; Bancong, Hartono (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to explore global patterns, trends, and research frontiers related to STEM (Science, Technology, Engineering, and Mathematics) education in early childhood through a bibliometric analysis. A total of 154 research articles published between 2020 and 2025 were retrieved from the Scopus database. The data were analyzed using VOSviewer and Biblioshiny to identify publication trends, leading countries, institutions, authors, journals, and thematic clusters in this field. The findings reveal a significant increase in research interest during the past five years, indicating the growing importance of early STEM education in fostering foundational scientific literacy and problem-solving skills among young children. The United States, China, and Australia were identified as the most productive countries, while key research themes include inquiry-based learning, STEM integration, teacher professional development, and gender equity in STEM. Emerging frontiers highlight the integration of digital technologies and play-based approaches to enhance early STEM learning experiences. This study contributes to a comprehensive understanding of the global landscape of early childhood STEM research and provides insights for future research directions and policy development in early education.